PELAKSANAAN PROGRAM BERAS UNTUK KELUARGA MISKIN (RASKIN) DALAM UPAYA PEMBERDAYAAN MASYARAKAT MISKIN DI KOTA BATU - Carmia Diahloka; Sulih Indra Dewi (Universitas Tribhuwana Tunggadewi, 2013)
The more and more of poor communities in the urban area has changing lane of target direction when disscussing about poverty. Urban poverty potentially become a source of social economic and social politic problems which can be fatal for society in a bigger scale. A qualitative method is used in this reseach based on reality in the field where a data collected by involved directly in the programme implementation. The result of this research showed that 1) Implementation of Raskin Programme in Batu barely having no difficulties, however there is still a lack of fund in Raskin distribution so regional government aiding a help through their APBD 2) expected role of the community will be very helpful for stimulation process in where at the same time boost empowerment of those poor community, 3) empowering process that happen in Raskin programme is showing a very healthy progress to combat poverty and giving a good impact to elevate their welfare and food self family.